2014
DOI: 10.1186/s13058-014-0476-9
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer anti-estrogen resistance 3 inhibits transforming growth factor β/Smad signaling and associates with favorable breast cancer disease outcomes

Abstract: IntroductionThis study helps to define the implications of breast cancer anti-estrogen resistance 3 (BCAR3) in breast cancer and extends the current understanding of its molecular mechanism of action. BCAR3 has been shown to promote cell proliferation, migration and attachment to extracellular matrix components. However, in a cohort of metastatic breast cancer patients who received tamoxifen treatment, high BCAR3 mRNA levels were associated with favorable progression-free survival outcome. These results sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 51 publications
2
24
0
Order By: Relevance
“…This can be determined by analyzing the correlation between BCAR3 expression and tumor subtype, tumor grade, metastasis, and overall survival in breast cancer patients. As mentioned previously, high levels of BCAR3 mRNA in patients treated with tamoxifen were found to correlate with increased progressionfree survival (Guo et al, 2014)…”
Section: Bcar3 As a Therapeutic Targetsupporting
confidence: 68%
See 4 more Smart Citations
“…This can be determined by analyzing the correlation between BCAR3 expression and tumor subtype, tumor grade, metastasis, and overall survival in breast cancer patients. As mentioned previously, high levels of BCAR3 mRNA in patients treated with tamoxifen were found to correlate with increased progressionfree survival (Guo et al, 2014)…”
Section: Bcar3 As a Therapeutic Targetsupporting
confidence: 68%
“…BCAR3 was originally identified as a gene that, when overexpressed in cell lines, conferred resistance to antiestrogens (VanAgthoven et al, 1998). However, one study reported that high BCAR3 mRNA levels associated with increased progressionfree survival in a cohort of ER+ breast cancer patients receiving tamoxifen treatment (Guo et al, 2014). This is potentially contradictory to what we know about BCAR3 function in vitro.…”
Section: Bcar3 As a Biomarkermentioning
confidence: 96%
See 3 more Smart Citations